Zarządzanie wiedzą - dylematy psychologiczne - Moczydłowska, Joanna (Knowledge management - psychological dilemmas, 2005)
The research of the knowledge management process and its importance for the development of business companies and other institutions is the area where psychology is becoming a partner of the management science. The analysis of the most essential concepts for knowledge management such as knowledge, intelligence, the process of study, aspiration and motivation can prove this point. The aim of this research is to present the psychological reflection on knowledge management as well as pointing out the dilemmas which can appear when adapt psychological perspective of this issue. The report presents the synthesis of the psychological output in the field of the cognition process research especially thinking, reasoning and problem solving. The postulate of avoiding using the concept “knowledge” as well as its using instead of the concept “information” has been motivated. The necessity of taking into the consideration of employees’ psychological restrictions in the field of generating, processing and knowledge transfer. Results from the level of their intelligence and personality has been pointed. The need of linking knowledge management and organizational stress prevention has been emphasized.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2005; nr 1064, s. 170-179